Sarcopenia and Health-related Quality of Life in Community-dwelling Older Adults - Nasrin Nasimi; Mohammad Hossein Dabbaghmanesgh; Mohammad Fararooei; Amirhossein Asadi; Marzieh Akbarzadeh; Zahra Sohrabi (Shiraz University of Medical Sciences, 2024)
Background: Sarcopenia, an age-related decline in muscle mass, strength, and function, contributes to various adverse health outcomes and physical impairments. This study aimed to investigate the association between sarcopenia components and health-related quality of life (HRQoL) among communitydwelling older adults.Methods: In this cross-sectional study, 501 adults aged 65 years or older participated. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia (AWGS) guideline. Muscle mass was measured by bioelectrical impedance analysis (BIA), muscle strength by hand dynamometer, and physical function by 4-m gait speed. The HRQoL was assessed using 12 item shortform healthy survey (SF-12) questionnaire.Results: There was a significant relationship between the sarcopenia and demographic characteristics (educational levels and smoking habits). After adjustment for age, sex, Body Mass Index, education level, smoking habits, and number of comorbidities, a significant relationship was observed between sarcopenia and physical components of HRQoL. According to multivariate linear regression, low muscle mass was negatively related to physical aspects of HRQoL. Low handgrip strength (HGS) and gait speed (GS) were inversely correlated to both physical and mental components of HRQoL.Conclusion: Our study highlighted the adverse impact of sarcopenia on HRQoL in elderly population. Reduction in muscle strength and physical performance not only affected physical aspects but also were linked with mental components of HRQoL. Therefore, it seems HGS and GS might be good indicators affecting all aspects of HRQoL in the elderly groups.